في موكب الإصلاح :‏ ‏صفحات من التواصل بين أعلام الإباضية و السيد محمد رشيد رضا من خلال مجلته (المنار) في فترة صدورها بين سنتي 1315-1354هـ - الشيباني, سلطان بن مبارك (ذاكرة عمان, 2015)
Keywords: Réformisme

The Individual Reaction to Western Modernization - Ghazal, Amal N. (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Redefining Ibāḍī Identity through Religious Discourse in the Time of the Nahḍa - Ziaka, Angeliki (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Islamic Modernisms: An Ibāḍī-Shīʿite Perspective - Modaressi, Hossein (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme

Science and Education: An Ibāḍī Project of Reform - Ghazal, Amal N. (Local and global Ibadi identities, 2019)
Keywords: Réformisme

Politics and Polemics. Ibāḍī Theology in North Africa in the Modern Period - Ghazal, Amal N. (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Réformisme

An Ottoman Pasha and the End of Empire: Sulayman al-Baruni and the Networks of Islamic Reform - Ghazal, Amal N. (Global Muslims in the Age of Steam and Print, 2014)
Keywords: Bārūnī, Sulaymān al- (1870-1940); Réformisme

The other frontiers of Arab nationalism: Ibadis, berbers, and the Arabist-Salafi Press in the Interwar period - Ghazal, Amal N. (International Journal of Middle East Studies, 2010)
On Abū Isḥāq Ibr. Iṭfayyish (Cairo), Abū ‘l-Yaqẓān Ibr. (Mīzāb), Hāshil al-Maskarī and his journal al-Falaq in Zanzibar.
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973); Aṭfiyyash, Ibrāhīm b. Muḥammad (1886-1965); Maskarī, Hāshil al-; Réformisme

Transcending Area Studies: Piecing Together the Cross-Regional Networks of Ibadi Islam - Ghazal, Amal N. (Comparative Studies of South Asia, Africa and the Middle East, 2014)
The area studies model is an impediment to the historical analysis of linkages and connections not governed by its geographical and conceptual boundaries. Its shortcomings are even more pronounced in the historiography of the modern period, when interactions and exchanges between different communities have changed dramatically, in both scale and scope. In the region loosely defined as the Middle East, the problem is further compounded by the collapse of the Ottoman order and the erection of state borders. The framework of methodological nationalism tied to those borders has been productive of certain kinds of histories and not others. In this intervention, Ghazal takes the case of Ibadis, their geographic distribution, political activism, and patterns of communication, to showcase the shortcomings of area studies as a model of historical analysis. A more viable alternative to spatially bounded analytical frames, Ghazal proposes, is the network.
Keywords: Réformisme